Digitization and Virtualization of Minahasan Bamboo Instruments: Development of a Culturally-Informed Virtual Studio Technology Plugin - Najoan, Xaverius; Neman, Meily Ivane Esther; Kembuan, Roger Allan Christian (CogITo Smart Journal, 2025)
Traditional musical instruments are an important component of intangible cultural heritage, yet many remain underrepresented in contemporary digital music production. In particular, Minahasan bamboo instruments face limited accessibility due to the lack of digital instrument representations. This study addresses this issue by developing a culturally informed Virtual Studio Technology (VST3) plugin that digitizes and simulates the characteristic sounds of Minahasan bamboo music. The proposed approach combines field recording, digital audio processing, and sample-based virtual instrument development using the JUCE framework. The resulting plugin was evaluated through functional, compatibility, performance, and cultural fidelity testing across multiple digital audio workstations. Experimental results demonstrate accurate MIDI-to-audio translation, low-latency performance, stable operation, and efficient CPU usage. User evaluations further confirm the authenticity of the sound and the usability of the interface. The findings indicate that VST-based digitization offers a practical and transferable solution for preserving traditional musical instruments while enabling their integration into modern music production workflows.